A Bibliometric Overview of the International Airports and Airlines ‘IAA’ Topic in Journals and Scientific Community. - Florido Benítez, Lázaro (MDPI, 2023)
Background: The purpose of this study is to provide an assessment of international airports and airlines, ‘IAAs’, and to organize and classify the literature on air transport to stage the importance of this topic and encourage future research in the projection of the aviation and tourism sectors. Methods: It is a bibliographic study, and this work focuses on IAA documents published in major international journals, conferences, and books from 2000 to 9 June 2021; this topic is scattered across various journals and has secondary data in many disciplines. Results: The findings suggest a new paradigm applied to the IAA topic and are classified in four first-order research streams: airports; airlines; connectivity; and competition. This study identifies new challenges and opportunities for researchers, airport and airline operators, and stakeholders to make better future decisions. Conclusions: There is no agreement on an explicit definition of the IAA concept that captures the true nature of this topic. For this reason, this article is innovative in the new IAA concept and in how it will possibly change the theoretical frameworks in future scientific research in the aviation and tourism sectors. This study has been needed to better understand the effectiveness, projection, and different business strategies to be adopted by researchers and organizations in the aviation and tourism future.
Keywords: Bibliometría; Aviación; Turismo; Airport; Airlines; Academics research; Universities; Disciplines